2007
DOI: 10.1111/j.1365-2958.2007.06088.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of gene regulation by the THI‐box riboswitch

Abstract: SummaryRiboswitches are genetic control elements located mainly within the 5Ј untranslated regions of messenger RNAs. These RNA elements undergo conformational changes that modulate gene expression upon binding of regulatory signals including vitamins, amino acids, nucleobases and uncharged tRNA. The thiamin pyrophosphate (TPP)-binding riboswitch (THI-box) is found in all three kingdoms of life and can regulate gene expression at the levels of premature termination of transcription, initiation of translation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 45 publications
3
48
1
Order By: Relevance
“…Although the C48-G67 closing base pair is thermodynamically favored at 1 M salt, our data suggest the 59 G48-C67 closing base pair, seen in the wild type, favors the interaction of magnesium with the RNA at pH 7.5. Consistent with our results, OntiverosPalacios et al (2008) showed that TPP binding is threefold weaker when guanine at position 48 is modified to cytosine (Ontiveros-Palacios et al 2008). Upon lowering the pH to 5.5, magnesium binding to the C48-G67 construct is restored to the level of the RNA WT (Fig.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Although the C48-G67 closing base pair is thermodynamically favored at 1 M salt, our data suggest the 59 G48-C67 closing base pair, seen in the wild type, favors the interaction of magnesium with the RNA at pH 7.5. Consistent with our results, OntiverosPalacios et al (2008) showed that TPP binding is threefold weaker when guanine at position 48 is modified to cytosine (Ontiveros-Palacios et al 2008). Upon lowering the pH to 5.5, magnesium binding to the C48-G67 construct is restored to the level of the RNA WT (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…This study examines the pyrophosphate sensor helix region of the thiC riboswitch RNA derived from Arabidopsis thaliana. Five bases in the pyrophosphate sensor domain are conserved (Thore et al 2006;Ontiveros-Palacios et al 2008). Positions C45, G48, and G64 are conserved bases in the helical stems and positions 65 and 66 are conserved in the 2 3 2 internal bulge (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…However, the β-galactosidase activity was decreased in the presence of ligand only when using fusions containing significant portions of the coding region (34), suggesting the presence of regulatory element(s) within the btuB ORF that negatively modulate the mRNA level in the absence of translating ribosomes (34). Together with recent studies (16,17), our data suggest that the thiM riboswitch uses a similar genetic regulating mechanism (SI Appendix, Fig. S3).…”
Section: Discussionmentioning
confidence: 70%
“…1C) is observed generally among riboswitches that control translation when inhibiting translation initiation. To address this question, we used the E. coli thiM thiamin pyrophosphate (TPP) riboswitch that previously was shown to act at the translational level (16,17). Although a strong TPP-dependent decrease in β-galactosidase activity was observed for the translational fusion in the presence of 500 μg/mL TPP, no such decrease was detected when the transcriptional construct was used (SI Appendix, Fig.…”
mentioning
confidence: 99%
“…Nonetheless, the mechanism by which the SAH riboswitch transduces ligand binding into a regulatory response is similar to other riboswitches (Wickiser et al 2005;Fuchs et al 2006;Ontiveros-Palacios et al 2008). Following transcription of the aptamer domain, the riboswitch reaches a folding branch point, each leading to the formation of one of two mutually exclusive hairpin structures in the downstream expression platform (Fig.…”
Section: Discussionmentioning
confidence: 99%